(untitled) (Olhar de Professor, 2021)
This text has as objective to analyze the contributions of the thinking of Paulo Freire (1921-1997) in the debate about authority and discipline on schoolar context. This question has been recaptured with emphasis over the last years in the country and has become materialized in the scope of the public polycies around the militarization of the public schools. In this sense, this article proposes to think about: would the militarization of the public schools be the only way out to schools reorganization around discipline and quality of education? The hipothesis is that Freire’s thought can help to build a counter offensive from a proposal that aims at authority and discipline, but, without leaving aside something fundamental on democracy: the freedom. This text’s itinerary is to present Paulo Freire’s life and work and, in the sequence, to analyze Freire’s concepts of authority, discipline, freedom and autonomy. One of Freire’s lessons is that authority should be at service of freedom and that way, dialogically, it will be possible to strengthen and defend a plural, democratic, with quality and as inalienable right to everyone public school.